Geometry‐Induced Dislocations in Coaxial Heterostructural Nanotubes. Issue 13 (11th February 2013) - Yoon, Aram; Park, Jun Young; Jeon, Jong‐Myeong; Cho, Yigil; Park, Jun Beom; Yi, Gyu‐Chul; Oh, Kyu Hwan; Han, Heung Nam; Kim, Miyoung
Abstract : Highly localized dislocations in GaN/ZnO hetero‐nanostructures are generated from the residual strain field by lattice mismatches at two interfaces: between the substrate and hetero‐nanostructures, and between the ZnO core and GaN shell. The local strain field is measured using tranmission electron microscopy, and the relationship between the nanostructure morphology and the highly localized dislocations is analyzed by a finite element method.